The classification of the Mahāyāna Sutras in the Maurice Courant Catalogue of the Bibliothèque Nationale de France - Qie, Yonghuan; Parra Valero, Pablo; Carpallo Bautista, Antonio (Revista General de Información y Documentación, 2022)
The Courant catalogue is one of the three catalogues published in the last century by the French sinologist Maurice Courant that collected a large part of the Chinese Buddhist books preserved in the National Library of France. Its contribution both to the library itself and to the scientific field is evident from the fact that researchers today continue to cite these catalogues in their works. This work focuses on the study of some of the Buddhist books included in this catalogue, in particular the series that covers the call numbers from Chinois 5727 to Chinois 6073, most of which deal with the Mahāyāna sutras, with the exception of the mixed sutras. The term sutra refers to the discourses of the Buddha, while the Mahāyāna sutra is the general term for the writings of Mahāyāna Buddhism. Based on this catalogue and taking some books of the Mahāyāna sutras as examples, the classification used by Courant and his thematic organisation of them is investigated. Maurice Courant completed the catalogue in the early 20th century, using a Western rather than a Chinese classification system. At that time there was no specific classification for Buddhist books and the proportion of Buddhist books in the traditional classification of Chinese books is small. Some of the categories of the sutras in Courant’s catalogue are erroneous for various objective and subjective reasons, which are explained throughout the paper.